Single Channel Electrogastrogram Frequency Domain Analysis and Correspondence to Brain Activity in a Resting State Condition - Sahroni, Alvin; Miladiyah, Isnatin; Adinandra, Sisdarmanto; Sofyan, Pramudya Rakhmadyansyah; Anora, Levina; Hanafi, Mhd. (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2025)
An electrogastrogram (EGG) is a well-known method to record gastric myoelectrical activity. However, some researchers believe that EGG measures the gastric slow wave and can be used as a surrogate for gastric motility, whereas others claim that EGG is flawed. Our proposed study broadens the scope of EGG research, particularly by offering the opportunity to observe gut-brain signaling pathways, which can enhance our understanding of brain properties and behavior in response to psychological changes. This study focuses on how to confirm single-channel EGG's setup with public datasets and previous studies and how to observe the relationship of gut-brain axis pathways. We gathered four subjects utilizing a 250 Hz bioamp to monitor brain wave activity on the head and scalp including gastric activity, and used Zenodo's EGG dataset for the confirmation phase. We placed single-channel electrodes around the stomach to investigate gastric myoelectrical activity and extracted the EGG's power spectrum using a specific band-pass filter (0.03 - 0.07 Hz). We extracted the EGG's power spectrum and dominant frequency as our main features. Regarding brain electricity activities, we applied the FIR filter to obtain each brain wave's properties. We found that each subject had different responses during pre- and postprandial, both from primary and secondary resources. We found that the increase in EGG activity caused a change in EEG properties, particularly in the alpha band (8-12 Hz). Additionally, the EEG P3 site in the parietal lobe followed the power change rates of the EGG between 0 to 0.015 of relative power. We conclude that P3 and slow-wave gastric movement from EGG correspond to each other and reflect gut-brain axis pathways. However, future studies with larger samples must strengthen our findings according to the gut-brain axis pathways in the P3 site and EGG